Hurricane Sandy - Initial Evaluation of Patient Characteristics. Issue Volume 34:Issue s1(2019) (May 2019) - Rosenthal, Marc; Dunne, Robert
Abstract : Introduction: Disaster medical team response by governmental and non-governmental responders is highly variable and poorly characterized. Each response is unique in terms of caseload, patient demographics, and medical needs encountered. This variability increases the difficulty of determining team member composition as well as supply and equipment needs. In an effort to demonstrate this issue, we have reviewed the National Disaster Medical Response to Hurricane Sandy. Methods: This project was a retrospective chart review of Hurricane Sandy data abstracted from the National Disaster Medical System (NDMS) Health Information Repository (HIR) medical records from the NDMS system response, and were abstracted for data including vital signs, ages, sex, chief complaint, and final impressions. In addition, length of stay among other parameters was abstracted. The data was analyzed using Microsoft Excel and Access with descriptive statistics. In addition, the results were compared to similar indices in a community emergency department and prior NDMS responses. Results: The results indicate a wide range of patient ages, chief complaints, and final impressions. The vast majority of patients seen by Disaster Medical Assistance Teams (DMAT) were stable with relatively low acuity issues. The total number of charts reviewed were 7, 905. Respiratory complaints were the most frequent at 845 patients followed by toxicology/injuries at 706 patients and mental health issues at 452 patients. In approximately 3, 400 patients, no diagnosis was present in the chart. Length of stay averaged below 1 hour and peak patient ages were between 50-60 with a significant number of infants less than 2 years. Discussion: Characterization of NDMS responses by DMATs and comparison with prior events and community emergency department caseloads can provide an insight into the needs of DMATs and other response organizations in future responses.